2008
DOI: 10.1007/s11096-008-9270-z
|View full text |Cite
|
Sign up to set email alerts
|

Stability of antineoplastic agents in use for home-based intravenous chemotherapy

Abstract: Considering the lack of data about cytotoxic drugs stability provided by the pharmaceutical companies and the difficulties in retrieving and interpreting the literature data, a consensus on the stability of cytotoxic drug preparations is essential for the current practice. With this approach, initiated for home hospitalisation, we propose in this study an initiative of the standardisation of stability data which offers a decision support for other centres.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Unfortunately, the stability of cytotoxic drug preparations is often unpredictable. A study of 34 intravenous cytotoxic drugs prepared in 6 hospital pharmacies of the Assistance Publique-Hôpitaux de Paris (AP-HP) hospitals found that stability varied by as much as 168 h, 28 Six anticancer drugs (alemtuzumab, azacitidine, bleomycin, mitomycin C, raltitrexed, and trastuzumab) were found to be stable for less than 30 h, indicating the necessity for an aseptic unit to be operational during weekends and off-hours if such drugs are to be used during these times.…”
Section: Compound Stabilitymentioning
confidence: 99%
“…Unfortunately, the stability of cytotoxic drug preparations is often unpredictable. A study of 34 intravenous cytotoxic drugs prepared in 6 hospital pharmacies of the Assistance Publique-Hôpitaux de Paris (AP-HP) hospitals found that stability varied by as much as 168 h, 28 Six anticancer drugs (alemtuzumab, azacitidine, bleomycin, mitomycin C, raltitrexed, and trastuzumab) were found to be stable for less than 30 h, indicating the necessity for an aseptic unit to be operational during weekends and off-hours if such drugs are to be used during these times.…”
Section: Compound Stabilitymentioning
confidence: 99%
“…0.9% sodium chloride, 5% dextrose in water), chemicals added to and/or already in the mixture (e.g. preservatives, solvent, excipients), storage time, exposure to oxygen, humidity and pH of drug . The potential impact of such factors on drug stability will be mentioned where applicable for 19 injectable chemotherapy drugs commonly used in veterinary medicine; however an extensive discussion of each factor is beyond the scope of this review (Table ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have assessed the response of the pharmaceutical industry to specific information requests from hospital pharmacy and community pharmacy including: the adequate storing conditions of a drug that was removed from its original container,16 the room temperature storage of drug products labelled for refrigeration17 18 or the stability of cytotoxic drug preparations 19. The results of these studies showed that a satisfactory response from the pharmaceutical industry was only provided for approximately 10% of the information requests;18 almost 20% manufacturers were unable to provide information about the stability of medications labelled for refrigeration that were inadvertently exposed to room temperature;17 and 30% manufacturers were unable to provide stability data for compounded anticancer drugs 19…”
Section: Introductionmentioning
confidence: 99%